Autecology of benthic diatom Striatella unipunctata (Lyngbye) C. A. Agardh, 1832 – indicator of organic water pollution (Black Sea and Sea of Japan) - L. I. Ryabushko (A. O. Kovalevsky Institute of Biology of the Southern Seas of RAS, 2021)
Analysis of long-term data (1987–2019) was carried out on the morphology and autecology of the benthic colonial large-cell species Striatella unipunctata (Lyngbye) C. A. Agardh, 1832 in the microphytobenthos of the Black Sea and Sea of Japan, including water areas of specially protected natural areas of Russia. The species is widely found on natural and artificial substrates in the Black Sea year-round, and in the Sea of Japan, at a water temperature down to −1.5 °C. St. unipunctata quantitative data were determined by direct cell counting in the Goryaev camera under light microscopes (LMs) Biolam L-212, Axioskop 40, and Olympus BX41. Species morphology, phytogeography, and ecology are described. The cell size range of populations is presented: for the Black Sea, valves 25–148 µm long, 8–22 µm wide, frustules 36.3–50.4 µm wide, 18–24 fibulae in 10 µm, and 7–8 girdle bands in 10 µm; for the Sea of Japan, valves 85–125 µm long, 12–21 µm wide, 7–8 girdle bands in 10 µm, 20–25 fibulae in 10 µm, frustules 32.0–34.3 µm long, 10–11 µm wide, and 25 fibulae in 10 µm. For the first time, St. unipunctata valves and frustules were studied in vivo under LMs, and frustule ultrastructure, under a scanning electron microscope (SEM). For the first time, quantitative indicators of the species populations from the Black Sea and Sea of Japan were compared. The morphology of the frustule ultrastructure of St. unipunctata was studied under a Hitachi SEM, model SU3500 (Japan), in Leica EM ACE200 gold-palladium-coated samples. In the Kazachya Bay of the Black Sea near the Oceanarium, the absolute maximum abundance was recorded – 41.6·10³ cells·cm−2 with a biomass of 1.73 mg·cm−2 in January (t = +6.9 °C) in the epizoon of the cultured mussel Mytilus galloprovincialis Lamarck, 1819 at a depth of 0.5 m at excessive organic pollution of water. The minimum values were of 0.26·10³ cells·cm−2 and 0.011 mg·cm−2, respectively, in July (t = +23.5 °C) at a depth of 2.5 m. In the Paris Bay (Russky Island) of the Sea of Japan in the water area of the Marine Mammal Research Base of the Primorsky Oceanarium (Vladivostok), the abundance in the asbestos plates periphyton was of 207·10³ cells·cm−2 in the summer. For the first time, unique micrographs of the species in vivo were obtained under a LM, and of purified frustules – under a SEM.